Anatomical investigation of flower of Butea monosperma Lam. - Muthuswamy, Ragunathan (Anc Sci Life, 2014)
BACKGROUND: Butea frondosa Roxb. and Koen. syn. Butea monosperma Lam. (Leguminosae or Fabaceae) is a tree grows up to the height of 8 m at the age 50 years. Its flowers are being used in traditional medicine for the treatment of ulcer, inflammation, hepatic disorder, and eye diseases. AIMS: The present study was aimed at establishing the microscopic characteristics of flower B. monosperma Lam. MATERIALS AND METHODS: Histological evaluation of flowers was done using standard procedures. Images of microscopic characters were taken at different magnifications using Nikon Labphoto 2 microscopic Unit. Perkin Elmer 5000 an atomic absorption spectrophotometer was employed for elemental analysis. RESULTS: In the study, microscopic characters of floral parts were investigated in transverse section and the flower powder. The current study reveals the presence of pollen grains, ovary (OV), and trichomes in their flower powder. Different cell components were studied, and their sizes were measured. Elemental analysis showed the presence of Zn 52.2 μg/g and Cu 36.3 μg/g were major contents, whereas Cr, Mn, and Pd were minor contents in dried flower powder. CONCLUSION: The current study paves the way to provide standard information related to the presence of essential elements in the flower. Microscopic characters of the flower and its quantitative measurement of cell components will help to identify the plant and also help to improvise the existing monograph of B. monosperma in the Ayurvedic pharmacopoeia.